Collaborative learning based on a micro-webserver remote test controller - José M. M. Ferreira (2009)
This paper presents a remote test workbench that was developed to support on-line assignments dealing with the IEEE 1149.1 standard test access port and boundary-scan architecture. The remote test controller is based on the DS80C400 networked microcontroller from Maxim-Dallas, which offers a very cost-effective solution to the development of micro-webservers enabling low-complexity data acquisition and control tasks. All remote experiments are integrated into Moodle in exactly the same way as the remaining courseware that is made available to the students. The use of Moodle facilitates the implementation of collaborative learning activities based on the remote test workbench, and the development of the workbench itself is the subject of a collaborative learning project involving students from the universities of Porto in Portugal and South Australia at Adelaide.